Macroeconomics - McEachern, William A. (Thomson/South-Western, 2006)
Succeed with the Study Guide for MACROECONOMICS: A CONTEMPORARY INTRODUCTION. This Study Guide includes chapter outlines, definitions of all terms, a bonus section with supplemental material, and a variety of true-false, multiple-choice, and discussion questions with answers